(3TQM QhVI Gdaghe aj fXe fbGjI GdYdhes - (3eMeO Hf CMeO Hf YHO GdMb GdSfHGWi GdTGaYjs
(3ChdgG (B:s
(3dLejY GdeMGejO hai CUdg HfGA Ydi GdQGLM s
(3BNQgG (B:s
(3eY eG GTJed Ydjg ef JgSjd GdebGUO hJcejd GdahGFO hGdUdGI hGdSdGe Ydi SjOfG eMeO NGJe GdfHjjf hGdeQSdjf hYdi Bdg hUMHg CLejYf s
(3GdfSNI HgG MhGTs
(3QhVI GdYdhe GfXQ cTa GdXfhf L(B1 (3U` (B929s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdeYGQa GdYGeIs